Relevansi Kandungan Informasi Komponen Arus Kas dan Laba dalam Memprediksi Arus Kas Masa Depan - Bandi Bandi; Rahmawati Rahmawati (Jurnal Akuntansi dan Bisnis, 2005)
Target of this research is to know do cash flow component which consist of operation current, financing current and investment current have ability of predict for cash flow in the future. Second, does profit also have ability to predict for cash flow in a future period. In line with research target and problem hence, this research is executed by using method archival in its data collecting. Result of coefficient of regression indicate that predictor earnings do not absolutely have ability of prediction which better than cash flow predictor. Result of calculation of MAPE, t test and F test give conclusion that fifth model that is model that included all cash flow component and of earnings more pre-eminent than the other model. Result of this research consistence with researches which have been done previously expressing that resolving of cash flow become current components operation cash, financing and investment will improve relationship and matching with theory.